TESTING AND STRATEGIES OF THE ANATOMAGE TABLE USE IN TEACHING PHYSICAL ANTHROPOLOGY - Kazoka, Dzintra; Pilmane, Mara (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
At the Department of Morphology, integrating the Anatomage Table (AT) into medical education is a supplementary resource to teach virtual Human Anatomy to medical students and their future professional and clinical careers. This study aimed to examine and test an AT in teaching a virtual Physical Anthropology course and assess the tutors’ beliefs and perceptions regarding using technology for teaching. Two tutors participated in the study from autumn 2022 until autumn 2023. Data were collected by tutors who followed specific methods to identify and measure anthropometrical points for evaluation. Tutors paid attention to the available virtual human body images for data collection, research, teaching and learning. Several anthropometrical measurements were performed and collected based on standard methods and positions in the table views. AT was mandatory to verify precise indicators’ location and confirm digital instruments for their detection over several human bodies. As part of this study, suggestions for the utilization of the AT to gather essential anthropometrical information have been prepared. Future studies can aim to generate unique methods and supplemental procedures for getting anthropometrical data in contact with AT and using this technology in teaching Physical Anthropology.